Solve for z t=c+czt

Math
t=c+czt
Rewrite the equation as c+czt=t.
c+czt=t
Subtract c from both sides of the equation.
czt=t-c
Divide each term by ct and simplify.
Tap for more steps…
Divide each term in czt=t-c by ct.
cztct=tct+-cct
Simplify cztct.
Tap for more steps…
Cancel the common factor of c.
Tap for more steps…
Cancel the common factor.
cztct=tct+-cct
Rewrite the expression.
ztt=tct+-cct
ztt=tct+-cct
Cancel the common factor of t.
Tap for more steps…
Cancel the common factor.
ztt=tct+-cct
Divide z by 1.
z=tct+-cct
z=tct+-cct
z=tct+-cct
Simplify each term.
Tap for more steps…
Cancel the common factor of t.
Tap for more steps…
Cancel the common factor.
z=tct+-cct
Rewrite the expression.
z=1c+-cct
z=1c+-cct
Cancel the common factor of c.
Tap for more steps…
Cancel the common factor.
z=1c+-cct
Rewrite the expression.
z=1c+-1t
z=1c+-1t
Move the negative in front of the fraction.
z=1c-1t
z=1c-1t
z=1c-1t
Solve for z t=c+czt

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top